MANAJEMEN RISIKO K3 MELALUI PENERAPAN METODE HIRADC PADA INDUSTRI BATU BATA KULIM - Siti Nurhaliza; Syahril Fajri; Agyl Septianta; Nazwa Fozlina Putri; Slamatul Ihsan; Rendi Randika (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
The brick manufacturing industry is one of the business sectors that has various potential hazards for workers, especially because most of the production processes are still carried out traditionally. This study aims to identify hazards, assess the level of risk, and evaluate the effectiveness of the application of the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method in controlling Occupational Safety and Health (K3) risks in the Kulim Brick Industry. The study used a qualitative approach with a phenomenological design. Data were obtained through in-depth interviews and direct observation of four informants consisting of business owners and workers at various stages of production. Analysis was carried out using the HIRADC method through hazard identification, risk assessment using a risk matrix, and determining control measures based on the risk control hierarchy. The results of the study indicate that there are various potential hazards in the processes of molding, transporting, arranging, and firing bricks. The risks found are categorized as moderate, high, and extreme, with the main hazards being exposure to dust and combustion smoke, hot temperatures, non-ergonomic work movements, excessive loads, and the risk of being caught in machinery. The industry lacks standard operating procedures (SOPs) for occupational health and safety (OHS), adequate personal protective equipment (PPE), and systematic risk control. Although some simple control measures exist, their effectiveness in reducing risk levels is limited. This study concludes that the implementation of the HIRADC method in the Kulim Brick Industry is suboptimal and needs to be improved through the development of SOPs, the provision of PPE, OHS training, and the strengthening of a more structured risk control system.